Genetic studies on growth and production traits in German Angora Rabbits under sub-temperate climatic conditions - RAHIM, ABDUL; RAJARAVINDRA, K S; CHATURVEDI, OM HARI; CHAUDHARY, RAJNI; SHARMA, S R (The Indian Journal of Animal Sciences, 2022)
This study aimed to assess the effect of genetic and non-genetic factors on growth, wool yield and wool characteristics of German Angora rabbit. Data was collected on 607 adult rabbits over a period of four years (2018-2021). The least squares means of body weights (g) at various ages, wool yield (g) at I, II, III and IV clip and wool characteristics assessed by staple length (cm) and fiber diameter (μ) were estimated. Sires of the rabbit progenies demonstrated highly significant effect (P<0.01) on the studied traits except wool characteristics. Sex of the rabbits had significant effect on body weight at 10th, 12th, 14th, 16th, 24th weeks of ages and wool yield at III clip, with greater estimates of females than the males for III clip, staple length, and 24th weeks body weight. Winter and autumn seasons were the most favourable seasons in comparison to summer season for estimated traits. Winter born kits had the highest body weights of 683±20.1, 961±24.3, 1263±27.5, 1484±34.0, 1735±37.1, 1942±40.1, 2136±36.9, 2232±36.7, 2341±37.4 and 2429±37.4 g and the summer born kits had the lowest body weights of 588±22.0, 820±27.2, 1037±31.2, 1307±38.0, 1515.79±41.0, 1696±44.1, 1847±41.4, 1920±41.0, 2034±42.4 and 2139±41.6 g, at biweekly interval from 6th to 24th, respectively. Rabbits with litter size less than six performed better in comparison to other groups for all growth traits and wool yield at I and III clip. The heritability estimates were found positive and high in magnitude for all growth traits, moderate for wool clip at different clips and very low for staple length. Genetic and phenotypic correlations were found to be very high and significant among growth traits and low to moderate among wool traits. The study revealed scope for further improvement in growth and wool yield by adopting selective breeding in the colony.